High dose CD11c-driven IL15 is sufficient to drive NK cell maturation and anti-tumor activity in a trans-presentation independent manner (2016)
The common gamma (?c)-chain cytokine interleukin 15 (IL15) is a multifunctional immune-modulator which impacts the generation, maturation and activity of many cell types of the innate, as well as the adaptive immune system, including natural killer (NK) and CD8+ T cells. Using a new series of transgenic mice, we analyzed the in vivo potential of IL15 as an immune-regulator when available at different concentrations or delivery modes, i.e. soluble monomer or complexed to its specific receptor a (Ra)-chain. We have identified distinct effects on selected IL15-responsive populations. While CD8+ T cells required complexed forms of IL15/IL15Ra for full functionality, mature NK populations were rescued in an IL15/IL15Ra-deficient environment by high levels of CD11c-restricted IL15. These IL15-conditions were sufficient to limit tumor formation in a lung metastasis model indicating that the NK cell populations were fully functional. These data underline the potential of "free" IL15 in the absence of Ra-complex as a powerful and specific immuno-modulator, which may be beneficial where selective immune-activation is desired.